Analysis of Patient Satisfaction with Pharmaceutical Services at Pharmacy Faeyza Farma Banyuwangi Regency - Rizalina Fajar Inzani; Fidi Setyawan; Hanik Mariana Dewi; Janik Kurniawati (Strada Journal of Pharmacy, 2021)
Pharmaceutical services are an integral part of the health system and are essential in realizing quality health for the community. This study used a quantitative descriptive approach to provide an objective picture of the condition of pharmaceutical services at Faeyza Farma Pharmacy in Banyuwangi Regency. Data were collected through questionnaires distributed to patients and families of patients who visited the pharmacy. Sampling was systematically randomized to ensure the representativeness of the population under study. The results showed that most patients were satisfied with pharmaceutical services at Faeyza Farma Pharmacy, with an average value of the gap between expectations and a tiny realization of -0.06. Based on patient satisfaction standards based on five dimensions, most patients are satisfied with the services at the Faeyza Farma Pharmacy, with an average satisfaction percentage of 80%, which is in the satisfied category. Based on the Importance and Performance Matrix Analysis, all question items in the questionnaire related to the five dimensions of pharmaceutical services at the Faeyza Farma Pharmacy are in quadrant II, which indicates that the service is good and needs to be maintained.